The Noice collection of Copper Inuit material culture / Fieldiana, Anthropology, new series, no.22 - VanStone, James W.; Field Museum of Natural History. (Chicago : Field Museum of Natural History, 1994)
The collections of the Field Museum of Natural History contain 234 ethnographic objects collected among the Copper Inuit of the Northwest Territories, Canada, in 1919-1921 by Harold Noice. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of Copper Inuit material culture, notably those of Stefansson (1914), Birket-Smith (1945), and Jenness (1946). Includes bibliographical references (p. 24-25). The collections of the Field Museum of Natural History contain 234 ethnographic objects collected among the Copper Inuit of the Northwest Territories, Canada, in 1919-1921 by Harold Noice. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of Copper Inuit material culture, notably those of Stefansson (1914), Birket-Smith (1945), and Jenness (1946). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).